Study of the adsorption capacity of Fe(II) dissolved in water by using a mineral rich in Manganese Dioxide (MnO2) from Colombia - Machado-Infante, Jhonnathan; Ramírez-Caballero, Gustavo; Barajas Meneses, Martha Juliana (DYNA, 2016)
In Colombia, a mineral rich in MnO2 is extracted from the mines of Mallama, Nariño. In this work we studied the adsorption capacity of this mineral for Fe(II) dissolved in aqueous solution of open systems. The characterization was done through ICP-AES, XRF and Raman spectroscopy. The effect of different pretreatments on the mineral with oxidizing agents such as KMnO4 and NaClO was evaluated. Studies of equilibrium and kinetics of adsorption showed that the mechanism fits well to the Langmuir isotherm and its kinetics to a model of pseudo-second order. At the conditions studied was found that the adsorption capacity for the mineral modified with KMnO4 and NaOCl were 59.209 and 51.279 mg/g respectively. It is concluded that the mineral is a potential alternative in water treatment.